A biomarker profile of elevated CSF p‐tau with normal tau PET is associated with increased tau accumulation rates on PET in early Alzheimer's disease. (20th December 2022) - Groot, Colin; Smith, Ruben; Stomrud, Erik; Binette, Alexa Pichet; Leuzy, Antoine; Wuestefeld, Anika; Wisse, Laura EM; Palmqvist, Sebastian; Janelidze, Shorena; Strandberg, Olof; Ossenkoppele, Rik; Hansson, Oskar
Abstract: Background: Different tau biomarkers become abnormal at different stages of Alzheimer's disease (AD), with CSF p‐tau typically being elevated at subthreshold levels of tau‐PET binding. To capitalize on the temporal order of tau biomarker‐abnormality and capture the earliest changes of tau accumulation, we selected a group of amyloid‐β‐positive (A+) individuals with elevated CSF p‐tau levels but negative tau‐PET scans and assessed longitudinal changes in tau‐PET, cortical thickness and cognitive decline. Method: Individuals without dementia (i.e., cognitively unimpaired (CU) or mild cognitive impairment, n=231) were selected from the BioFINDER‐2 study. These subjects were categorized into biomarker groups based on Gaussian mixture modelling to determine cut‐offs for abnormal CSF Aβ42/40 (A; <0.078), CSF p‐tau217 (P; >110 pg/ml) and [ 18 F]RO948 tau‐PET SUVR within a temporal meta‐ROI (T; SUVR >1.40). Resulting groups were: A+P‐T‐ (concordant, n=30), A+P+T‐ (discordant, n=48) and A+P+T+ (concordant, n=18). We additionally used 135 A‐ CU individuals (A‐ CU) as a reference group (Tables 1 and 2). Differences in annual change in regional tau‐PET SUVR, cortical thickness and cognition between the A+P+T‐ group and the other groups were assessed using general linear models, adjusted for age, sex, clinical diagnosis and (for cognitive measures) education. Result: Longitudinal change in tau‐PET was faster in the A+P+T‐ group than in the A‐ CU and A+P‐T‐ groups across medial temporal and neocortical regions, with the medial temporal increases being more pronounced. The A+P+T‐ group showed slower rate of increases in tau‐PET compared to the A+P+T+ group, primarily in neocortical regions (Figures 1 and 2). We did not detect differences in yearly change in cortical thickness (Figure 3) or in cognitive decline (Figure 3) between the A+P+T‐ and A+P‐T‐ groups. The A+P+T+ group, however, showed faster cognitive decline compared to all other groups. Conclusion: These findings suggest that the A+P+T‐ biomarker profile is associated with early tau accumulation, and with relative sparing of cortical thinning and cognitive decline compared to A+P+T+ individuals. Therefore, the A+P+T‐ group represents an interesting target‐group for early anti‐tau interventions and for examining the emergence of tau aggregates in early AD.